Prohibition & resistance: a socio-political exploration of the changing dynamics of the southern African cannabis trade, c. 1850 - the present - Paterson, Craig J (Rhodes University, Faculty of Humanities, Department of History, 2010)
Looking primarily at the social and political trends in South Africa over the course of the last century and a half, this thesis explores how these trends have contributed to the establishment of the southern Africa cannabis complex. Through an examination of the influence which the colonial paradigm based on Social Darwinian thinking had on the understanding of the cannabis plant in southern Africa, it is argued that cannabis prohibition and apartheid laws rested on the same ideological foundation. This thesis goes on to argue that the dynamics of cannabis production and trade can be understood in terms of the interplay between the two themes of 'prohibition' and 'resistance'. Prohibition is not only understood to refer to cannabis laws, but also to the proscription of inter-racial contact and segregation dictated by the apartheid regime. Resistance, then, refers to both resistance to apartheid and resistance to cannabis laws in this thesis. Including discussions on the hippie movement and development of the world trade, the anti-apartheid movement, the successful implementation of import substitution strategies in Europe and North America from the 1980's, and South Africa's incorporation into the global trade, this thesis illustrates how the apartheid system (and its collapse) influenced the region's cannabis trade.
Keywords: Cannabis -- Government policy -- Africa, Southern -- History -- 19th century; Cannabis -- Government policy -- Africa, Southern -- History -- 20th century; Cannabis -- Law and legislation -- Africa, Southern -- History -- 20th century; Drugs -- Government policy -- Africa, Southern -- History -- 19th century; Drugs -- Government policy -- Africa, Southern -- History -- 20th century; Drugs -- Law and legislation -- Africa, Southern -- History -- 19th century; Drugs -- Law and legislation -- Africa, Southern -- History -- 20th century; Drug traffic -- Africa, Southern -- History -- 19th century; Drug traffic -- Africa, Southern -- History -- 20th century Substance abuse -- Social aspects -- Africa, Southern